TEOLOGI HAKIMIYAH: BENIH RADIKALISME ISLAM - Iman Fauzi Ghifarie (Islam Realitas: Journal of Islamic and Social Studies, 2016)
This article examines the theological issues called hakimiyah as the seeds of extremism, fundamentalism, radicalism religion (Islam) that manifests itself in the behavior and acts of violence in the name of religion. The rise of radicalism among young people in the form of violence, terrorism, suicide bombing is coming from theology hakimiyah and Istisyhad doctrine (martyrdom) in order to get guarantee into heaven surrounded by 40 angels. It is because, they always spread hatred and hostility and beliefe to takfiri concept (infidelity) to resolve any different opinion,a belief that led to vigilante, even to take the life of another person as the main ticket to heaven. If the actions and behaviors that hurt the conscience and the humanitarian aspect continues to be done systematically, and sustained by the younger generation, then what would the fate of Mother Earth become? Of course, it is possible to give the birth of the Islamic State of Indonesia Malayasia. Meanwhile, Islam forbids any acts that damage, destroy, injure, and kill for no good reason. Even in a war, moral principles, morality, and ethics should be a guide and reference. Radicalism, terrorism, limbs and destruction have no religion nor country. Everyone who embrace the ideology which spread terror to the people who live safely, and bring damage to plants and animals are terrorist. No one can give any sentence of punishment "deviant," "infidel," "kill" to the group which have different understanding, except Allah, the supreme judges. When we do that kind of behavior and actions, then we are more powerful than God. Tulisan ini mengkaji persoalan teologi hakimiyah sebagai benih ekstremisme, fundamentalisme, radikalisme agama (Islam) yang mewujud dalam perilaku, tindakan kekerasan atas nama agama. Maraknya gerakan radikalisme di kalangan anak muda dalam bentuk aksi kekerasan, terorisme, bom bunuh diri ini yang bersumber dari teologi hakimiyah dan doktrin Istisyhad (mati syahid) demi mendapatkan jaminan masuk surga yang dikelilingi 40 bidadari.Pasalnya, mereka selalu menebarkan kebencian, permusuhan dengan memengang teguh pemahaman takfiri (pengkafiran) untuk menyelesaikan setiap perbedaan pendapat, keyakinan yang berujung pada cara main hakim sendiri, hingga menghilangkan nyawa orang lain sebagai tiket utama masuk surga. Jika tindakan dan perilaku yang melukai aspek kemanusiaan dan hati nurani ini terus dilakukan secara sistematis, berkelanjutan oleh generasi muda, maka apa jadinya nasib Bumi Pertiwi. Tentunya, tidak menutup kemungkinan akan lahirnya Negara Islam Indonesia Malayasia.Padahal, ajaran Islam mengharamkan setiap perbuatan yang merusak, membinasakan, melukai, dan membunuh tanpa alasan yang benar. Dalam peperangan sekalipun, prinsip-prinsip moral, akhlaq, dan etika harus dijadikan pedoman dan acuan. Radikalisme, terorisme, ekstremitas dan pengrusakan tidak punya agama dan tidak pula negara. Setiap orang yang menganut ideologi yang menebarkan teror kepada orang-orang yang hidup aman, serta merusak tumbuhan dan hewan adalah teroris.Tiada seseorang yang dapat memberikan penyebutan hukuman “sesat,” “kafir,” “bunuh” terhadap kelompok yang berbeda pemahaman, keyakinan kecuali hakim yang maha tinggi, Allah Swt. Bila perilaku dan tindakan itu kita lakukan, maka kita lebih berkuasa dari Tuhan.